Heroes and antiheroes in the tales of Zola and the painting of Manet (Colloquia Comparativa Litterarum, 2025)
In literature just as in the art of painting, the representation of the romantic or pictorial hero is dependent on an antihero who designates, by the narration of facts or by the evocation of pictorial signs, the relationship, the influence or effect of one on the other. In Zola's tale The Convent we have tried to analyse the relationship between two little girls with different aspects in their behaviour by showing the link between their descriptions and the paintings by Manet. Since Zola and Manet are considered to be very good friends, this explains the inspiration they drew on from each other through their literary and artistic creations which contain echoes and correspondences, among other things, in the evocation of the status of the hero and the antihero.
Keywords: Zola; Manet; hero, antihero; correspondences; education; identity